2012
DOI: 10.1179/1743132812y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic outcome in patients after polymethyl-methacrylate (PMMA) cranioplasty — a questionnaire-based single-centre study

Abstract: OBJECTIVES: Acquired skull deformities are common and most likely treated surgically by cranioplasty. Since data on patient aesthetic outcome after cranioplasty are rare in literature, we aimed to assess patient satisfaction after polymethyl-methacrylate (PMMA) cranioplasty in this study using a questionnaire. METHODS: A patient questionnaire was developed to evaluate the grade of satisfaction after surgery. After approval by the institutional ethical review board, we were allowed to send to all 115 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…As shown in previous studies, cosmetic results matter to patients, especially in the frontotemporal region. 14 , 26 It has been shown that even a dent or irregularity of the cranioplasty may jeopardize the success of the surgery. 26 It was discovered that TCUS imaging may be painful within the first days after surgery, which is explained by the postoperative pain over the wound incision, and should be kept in mind when performed at bedside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in previous studies, cosmetic results matter to patients, especially in the frontotemporal region. 14 , 26 It has been shown that even a dent or irregularity of the cranioplasty may jeopardize the success of the surgery. 26 It was discovered that TCUS imaging may be painful within the first days after surgery, which is explained by the postoperative pain over the wound incision, and should be kept in mind when performed at bedside.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 26 It has been shown that even a dent or irregularity of the cranioplasty may jeopardize the success of the surgery. 26 It was discovered that TCUS imaging may be painful within the first days after surgery, which is explained by the postoperative pain over the wound incision, and should be kept in mind when performed at bedside. Our data showed that during outpatient follow-up there was no more pain after recovery from surgery and all patients enjoyed the opportunity to see the patent bypass together with the health care provider in real time.…”
Section: Discussionmentioning
confidence: 99%
“…The major skull growth occurs in the first 2 years, achieving about 84% of the adult size, with a strong deceleration after that age. Even * As proposed by Fischer et al 8 † Implant size was assessed objectively from radiological images and postoperative treatment from patient records. The slice of greatest cross-sectional area of the defect was chosen for size analysis: small, medium, and large defects were defined as ≤ 50 cm 2 , 50-100 cm 2 , and ≥ 100 cm 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were strictly followed-up with serial clinical evaluations at 7, 14, 21, and 28 days, a CT scan at 6 months after the surgery, and clinical evaluation 12 months later. All families were administered a questionnaire (proposed by Fischer et al) 8 to assess how the patient (or parent in very young patients) judged the aesthetic result ( Table 2). The study was performed with approval from the Giannina Gaslini Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Given this risk, an elective cranioplasty may offer a better cosmetic outcome for the patient. 8 Determination of this effect will of course require further evaluation with longer follow-up of a larger cohort of patients.…”
Section: Discussionmentioning
confidence: 99%